If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4=-3x+4
We move all terms to the left:
3x-4-(-3x+4)=0
We get rid of parentheses
3x+3x-4-4=0
We add all the numbers together, and all the variables
6x-8=0
We move all terms containing x to the left, all other terms to the right
6x=8
x=8/6
x=1+1/3
| -18-9x=30-6x | | 0.3x-10=1.1-22 | | 17x+11=13x-18 | | x(2x+7)=52 | | x+4=17= | | 11x-185=-x+139 | | 6.2z+1=5.5+4z | | 3(n–2)=15 | | X-65=5x+31 | | 6x-48=7x-7 | | -8y+10y=150 | | X+13=-2x+1 | | 8s+2s=10 | | -0,77=-0,1x-0.45 | | b−7/4=−2/3 | | 6x-47=7x-7 | | 2n+2=-124 | | 6x=x+50= | | b−47 =−32 | | 2.2n=3.85 | | x+9=(2x) | | 3x=3x-22 | | 4.5y=11-2.5y | | 7x-3+6x=127 | | 29-p=3 | | .5x+15+2x-50=180 | | 1/4n=2.75 | | 5x-17=2×-50 | | 4.5y=11-2.4y | | 0.75x0.8=0.6 | | 1+7+2+6+9+4+n=37 | | 9x-1=6x+18 |